2020
DOI: 10.1177/1120672120926453
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the far peripheral retina of normal eyes by ultra-wide field fluorescein angiography

Abstract: Purpose The appearance of the far peripheral retina in normal eyes was observed using an Optos ultra-wide field fluorescein angiography imaging system. Methods A cross-sectional study of ultra-wide field pseudocolor and angiography images obtained using the Optos 200Tx. Four different non-vascular and six vascular-associated fluorescence features in far peripheral retina were analyzed. Results A total of 166 eyes in 83 patients met the inclusion criteria. The mean patient age was 40.78 ± 10.94 years (range: 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“… 1 Another study reported the appearance of a mottled fluorescent band in the far peripheral retina in 42.17%, ground glass hyper fluorescence in 85.34%, and late-phase slight leakage in 32.53% of normal eyes. 2 The mottled fluorescent band can occur with vascular leakage simultaneously or separately. 1 The molecular weight of fluorescein is 389.38 g/mol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Another study reported the appearance of a mottled fluorescent band in the far peripheral retina in 42.17%, ground glass hyper fluorescence in 85.34%, and late-phase slight leakage in 32.53% of normal eyes. 2 The mottled fluorescent band can occur with vascular leakage simultaneously or separately. 1 The molecular weight of fluorescein is 389.38 g/mol.…”
Section: Discussionmentioning
confidence: 99%
“…1), was a recently reported finding observed occasionally in normal eyes on ultra-widefield fluorescein angiography (UWFA). 1,2 Since the contrast medium leaks at the far peripheral part of the retina, it is difficult to observe in a regular fundus examination. Therefore, the effect of aging on PRL and the relationship between PRL and various diseases are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies ranged in their commentary on retinal leakage, with some that did not appear to observe any leakage, and others that identified leakage in up to 46.9% of patients. 20 -25 The studies that did find leakage did not describe the extent of the leakage in a systemic fashion as we did, or they discovered only very mild cases. 21 -23 The cases of far peripheral leakage shown in our patients appeared more extensive than most current descriptions in “normal” eyes, and instances of midperipheral or posterior pole leakage as seen in some of our cases were not described in case series of “normal” eyes.…”
Section: Discussionmentioning
confidence: 69%
“…We were able, however, to compare our findings to previously published studies of ultra-widefield FA findings in "normal" eyes. [20][21][22][23][24][25] We note that none of those studies imaged patients without a clinical indication, which is why we placed the word normal in quotation marks. Those studies ranged in their commentary on retinal leakage, with some that did not appear to observe any leakage, and others that identified leakage in up to 46.9% of patients.…”
Section: Discussionmentioning
confidence: 99%